Computation of Energy Absorption and Residual Voltage in a Fourth Rail LRT Station Arresters in EMTP-RV: A Comparative Study - Abd Rahman F.A.; Ab Kadir M.Z.A.; Ungku Amirulddin U.A.; Osman M. (Springer Science and Business Media Deutschland GmbH, 2023)
This paper presents a study on the performance of a fourth rail direct current (DC) urban transit affected by an indirect lightning strike. The indirect lightning strike was replicated and represented by a lightning-induced overvoltage by means of the Rusck model, with the sum of two Heidler functions as its lightning channel base current input, on a perfect conducting ground. This study aims to determine whether an indirect lightning strike has any influence with regard to the performance of the LRT Kelana Jaya line, a fourth rail DC urban transit station arrester. The simulations were carried out using the Electromagnetic Transients ProgramRestructured Version (EMTPRV), which includes the comparison performance results between the 3EB4-010 arrester and PDTA09 arrester when induced by a 90 kA (9/200 s). The results demonstrated that the PDTA09 arrester showed better coordination with the insulated rail bracket of the fourth rail. It allowed a lower residual voltage and a more dynamic response, eventually resulting in better voltage gradient in the pre-breakdown region and decreased residual voltage ratio in the high current region. 2021, The Author(s).